2018
DOI: 10.29333/ejmste/90265
|View full text |Cite
|
Sign up to set email alerts
|

How do Students Perceived Computerized Feedback as Effective?

Abstract: Feedback plays an important role in fostering deep learning. It is widely recognized as one of the most powerful influences on students' learning. Meanwhile, timeliness is one of the important elements for feedback to be effective. In line with the technology development, the trend of feedback delivery has been shifted from conventional written and oral feedback to computerized feedback. It can be planned and delivered to students in a timely manner. To fully utilize the advantage of computerized feedback, stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Feedback is information provided to a student related to their skills or demonstrated performance during the completion of a task, usually after instruction (Hattie and Timperley, 2007). Feedback has been identified as a factor that can influence student performance (Fui and Lian, 2018;Martínez and Vargas, 2014;Uribe and Vaughan, 2017;Wisniewski et al, 2020) by allowing the students to identify what they need to achieve success according to what is expected of them, self-evaluating their learning and thinking on their actions and consequences, allowing them to reach goals and objectives. Likewise, it has been identified that little or ineffective feedback can lead to school dropout (Wisniewski et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Feedback is information provided to a student related to their skills or demonstrated performance during the completion of a task, usually after instruction (Hattie and Timperley, 2007). Feedback has been identified as a factor that can influence student performance (Fui and Lian, 2018;Martínez and Vargas, 2014;Uribe and Vaughan, 2017;Wisniewski et al, 2020) by allowing the students to identify what they need to achieve success according to what is expected of them, self-evaluating their learning and thinking on their actions and consequences, allowing them to reach goals and objectives. Likewise, it has been identified that little or ineffective feedback can lead to school dropout (Wisniewski et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Nahadi, Firman and Farina (2015) reported that students became enthusiastic, motivated, and more active in learning after being given feedback. As a result, feedback would make students learn a topic indepth (Fui & Lian, 2018).…”
Section: Introductionmentioning
confidence: 99%